Does imagination compensate for the need for touch in 360-virtual shopping?. (June 2023) - Ruusunen, Nino; Hallikainen, Heli; Laukkanen, Tommi
Abstract: The inability to touch products is a fundamental shortcoming in online shopping because humans typically use the sense of touch to evaluate the utilitarian product functionality and to obtain hedonic sensory enjoyment, which the instrumental and autotelic need for touch capture. This study of 900 consumers looks at the interplay between need for touch and imagination to study how imagination compensates for the lack of touch when consumers shop in a 360-virtual store. The study finds that while telepresence of a 360-virtual store improves consumer attitudes toward virtual shopping, the need for hedonic sensory enjoyment – autotelic need for touch – significantly reduces this effect. Further, imagination can compensate for the need for touch; yet this finding holds only for the instrumental need for touch, not for the autotelic need for touch. Consequently, we conclude that imagination can compensate for the utilitarian need to touch products in a 360-virtual store. Highlights: Examines how imagination shapes consumer's need for touch in 360-virtual shopping. Telepresence improves consumer attitudes toward 360-virtual shopping. Need for sensory enjoyment through touch reduces this effect remarkably. Vivid imagination can compensate for the lack of touch. Imagination compensates utilitarian but not hedonic dimension of need for touch.